2020
DOI: 10.1123/jsm.2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in the Relationship Between Legacies and Support: A Longitudinal Case Study in Rio 2016 Olympic Games

Abstract: The purpose of this research was to describe temporal variations in Rio residents’ support for the 2016 Olympic Games and in the relationship between perceptions of legacies and support for the event. Drawing on social exchange theory, perceptions (expectations and evaluations) of tangible, intangible, and environmental legacies should affect support intentions. A longitudinal trend study was designed. Four multistage stratified random samples of Rio residents were surveyed in 2012 (n = 900), 2014 (n = 900), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 70 publications
(127 reference statements)
4
46
4
Order By: Relevance
“…The IOC can adopt a broader perspective and promote respect and excellence beyond sport performance. For instance, recent investigations have shown that social and environmental legacies are the least expected ones by local residents as a consequence of hosting the Olympic Games (Rocha, 2020;Rocha et al, 2017). This seems to indicate that people do not see much excellence in the Games to promote respect for social and environmental issues.…”
Section: Discussionmentioning
confidence: 99%
“…The IOC can adopt a broader perspective and promote respect and excellence beyond sport performance. For instance, recent investigations have shown that social and environmental legacies are the least expected ones by local residents as a consequence of hosting the Olympic Games (Rocha, 2020;Rocha et al, 2017). This seems to indicate that people do not see much excellence in the Games to promote respect for social and environmental issues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite previous studies with more than one wave of data collection tend to show participant attrition (e.g. Rocha, 2020; Lee et al , 2013), it is important that future studies maintain contact after the first data collection and provide positive survey experiences (e.g. acknowledgment messages, information about the progress of the study, etc.)…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…Identifying host city residents' perceptions is vital for the sustainable development of sport events and cities (Ma et al , 2011, 2013). Notwithstanding, with the exception of one recent publication (Rocha, 2020), previous studies on the 2016 Rio Olympic Games have focussed on short-term social consequences for the local community. From a theoretical point a view, understanding citizens' perceptions of the event throughout time is important to help clarify social exchanges.…”
Section: Introductionmentioning
confidence: 99%
“…As result, our findings contribute to the lack of literature on post-event resident perspectives, reinforcing their role as an expression of mobility (perceptual or cognitive mobility) and on staging such events (Hiller 2018). In addition, the importance of post-event resident studies should remain to be strengthened, allowing a better understanding the process of how support is constructed and/or deconstructed in host communities (Rocha 2020).…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%